Analisis Faktor yang Berpengaruh Terhadap Kepercayaan dan Kepuasan Nasabah Pengguna Mobile Banking - Rojuaniah, Rojuaniah; Anugraheni, Suci; Syah, Tantri Yanuar Rahmat; Havidz, Ikramina Larasati Hazrati; Sari, Bayu Mayang (Universitas Batanghari Jambi, 2024)
Technology has made banking more user-friendly. Mobile banking a type of internet banking uses mobile devices to conduct financial transactions. Mobile banking makes banking easier and faster. To meet consumer expectations and build trust, loyalty, and happiness, mobile banking must be of high quality. Digital banking customers prioritize privacy and security, therefore banks must address these concerns. To reduce these concerns and retain customers, banks must provide excellent service. The purpose of this study is to analyze the effect of the overall trust dimension in explaining the mediator role of the trust variable in shaping customer satisfaction. Before the research, validity and reliability tests were carried out on each statement using Structural Equation Modeling (SEM) PLS. In this study, 165 government bank customers in Indonesia were involved as respondents. Based on the results of research that has been conducted, there is a significant positive influence between service quality, information quality, system quality, Structural assurance, Task Characteristic, Perceived of usefulness, Perceived ease of use on customer trust. This influence shows that the better customer trust, the higher customer satisfaction. Improving system quality, information quality, in mobile banking services will help companies strengthen customer trust and increase perceptions of service usefulness, leading to more positive and effective interactions.